A new approach to alpha-magnetic particles with flows by spherical frame - Körpınar, Talat (AMER SCIENTIFIC PUBLISHERS, 2018)
In this work, we investigate alpha-magnetic particles by inextensible flows in sphere. We have the new results for inextensible flows of alpha-magnetic particles. Also, we characterize flows of electric field by a Lorentz equation. Finally, we obtain an evolution equation of electric field in sphere and we obtain magnetic flux density for this magnetic particles with some expression.
Keywords: Inextensible Flows; Sabban Frame